From no body to some bodies: forms of mourning and melancholia in Jenny Boully's The Body and [one love affair]*. Issue 4 (2nd April 2020) - Maxwell, Kristi
ABSTRACT: The essay explores footnotes and endnotes as poetic forms in Jenny Boully's The Body and [ one love affair ]*. In The Body, Boully radically foregrounds the footnote by making it the sole textual component on the page. The essay argues that Boully uses footnotes and endnotes to enact textual performance, dramatising psychological reactions to a missing body by staging repression and the return of the repressed through alternately subsuming and subsiding footnotes and the covering over (more or less successfully) of the missing body of a dead lover who is figured in the blank textual body. Whereas The Body and its form are motivated by the tenets of melancholia, in her second book, [ one love affair ] *, Boully stages processes of mourning. Following Jeffrey Adams, the essay considers intertextuality in terms of 'aesthetic object-relating', arguing that palimpsest and endnotes perform a reactivation of object-relating and help the speaker of the poems reinvest in relationships with other subjects rather than withdraw from such investments because of an inability to grieve the lost object.